2016
DOI: 10.15517/rbt.v63i1.23100
|View full text |Cite
|
Sign up to set email alerts
|

Rasgos oceanográficos en el Golfo Dulce, Pacífico de Costa Rica: una revisión para la toma de decisiones en conservación marina

Abstract: Se indagó, de septiembre del 2005 a noviembre del 2007, las propiedades oceanográficas físicas, químicas y biológicas (zooplancton) más relevantes del Golfo Dulce, Pacífico Sur de Costa Rica, y las tipologías meteorológicas de la zona, con el objetivo de analizarlas y hacerlas disponibles como referencia en el establecimiento de actividades adecuadas para su conservación, dado que es un ecosistema acuático único en Costa Rica. El patrón de circulación de las aguas en el Golfo Dulce es el típico de estuarios ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
2
15
1
3
Order By: Relevance
“…In addition to the protective bathymetry, the inner basin is sheltered by the geographic shape of Golfo Dulce, which hooks strongly to the left, further limiting the effects of oceanic currents and hydrographic exchange (Svendsen et al, 2006). As a tropical region, the climate is bimodal, with seasonality based on monthly precipitation: dry (<300‐mm rainfall, December–April) and rainy (>500‐mm rainfall, May–November; Morales‐Ramírez et al, 2015). Air temperatures are generally warm, averaging 21–33.5°C (Lobo et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the protective bathymetry, the inner basin is sheltered by the geographic shape of Golfo Dulce, which hooks strongly to the left, further limiting the effects of oceanic currents and hydrographic exchange (Svendsen et al, 2006). As a tropical region, the climate is bimodal, with seasonality based on monthly precipitation: dry (<300‐mm rainfall, December–April) and rainy (>500‐mm rainfall, May–November; Morales‐Ramírez et al, 2015). Air temperatures are generally warm, averaging 21–33.5°C (Lobo et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Their abundance appears high when compared to offshore waters. Another survey (Morales-Ramírez et al, 2015) reported dominance (44 to 84 %) of copepods such as Oncaea mediterranea, Oithona plumifera, Acrocalanus gibber, Paracalanus parvus, P. aculeatus and Centropages furcatus. The gelatinous zooplankton was also studied and 41 species were identified of which 33 were cnidarians, six were thalaceans and two were ctenophores (Morales-Ramírez & Nowaczyk, 2006).…”
Section: The R/v Victor Hensen Faunal Survey and Other Studiesmentioning
confidence: 98%
“…A comprehensive study of water parameters along Golfo Dulce was conducted between 2005 and 2007 by Morales-Ramírez et al (2015) and included an evaluation of rainfall, currents, and nutrient concentrations. Rainfall ranged from 100 to near 700 mm/month.…”
Section: Temperature Oxygen and Salinity Profilesmentioning
confidence: 99%
“…than does Golfo Dulce (1028 spp. : Morales-Ramírez 2011 ) or Isla del Coco (1688 spp. : Cortés 2012 ), but about the same as what is currently known for Bahía Culebra (577 spp: Cortés et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%